Effect of Social Capital on Firm Performance: An Empirical Study of Small Enterprises in Sri Lanka (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
The purpose of this study is to examine the impact of social capital on the performance of Small Enterprises (SEs) in an emerging economy, Sri Lanka. The study adopts a survey design and cross-sectional data collected by administering 200 questionnaires conducting face to face interviews. The social capital was measured by three dimensions namely, structural, relational, and conative social capital. The data were analyzed using Partial Least Squares-Structural Equation Modelling. The results show that structural and cognitive social capital had a positive significant impact on the performance of SEs while relational social capital had demonstrated a negative statistically significant impact on the performance of SEs. This implies that the managers of SEs emphasize the social capital as a means to a source of finance and resources and access to business and market information by maintaining close ties with the stakeholders to achieve a competitive advantage. The findings will be useful for the owners/managers of SEs who should share their knowledge, opportunities, and resources with their suppliers, customers as well as employees of the organization such that they should try to share their goals and achieve success together with parties who are related and interested in the business.